PERAN PEREMPUAN DALAM SILSILAH YESUS: Kajian Hermeneutik Matius 1:1-17 dan Implikasinya Bagi Jemaat - Ruauw, Paskalita Kimberly Jaclin; Suoth, Vanny N. (Educatio Christi, 2023)
This article was studied by carrying out hermeneutic work using historical critical methods which discussed the role of women in the genealogy of Jesus as a reference for understanding the role that was given in the presence of the Savior figure. Genealogies usually do not include the names of women or mother figures, Tamar, Rahab, Ruth, Bathsheba and Mary are the women included in the Genealogy of Jesus. With their different backgrounds, even some of them living in sin, it certainly shows that God's authority can use anyone regardless of background. But the role they provide is through courage, loyalty and faith despite their limitations and shortcomings. This is what the GMIM "Sion Sentrum" Sendangan Kawangkoan Region congregation must understand in looking at the role of women but also for women to play a role in congregational life.